Shear behavior of coarse aggregates for dam construction under varied stress paths - Liu Hanlong; Deng An; Shen Yang (Water Science and Engineering, 2008)
Coarse aggregates are the major infrastructure materials of concrete-faced rock-fill dams and are consolidated to bear upper and lateral loads. With the increase of dam height, high confining pressure and complex stress states complicate the shear behavior of coarse aggregates, and thus impede the high dam's proper construction, operation and maintenance. An experimental program was conducted to study the shear behavior of dam coarse aggregates using a large-scale triaxial shear apparatus. Through triaxial shear tests, the strain-stress behaviors of aggregates were observed under constant confining pressures: 300 kPa, 600 kPa, 900 kPa and 1200 kPa. Shear strengths and aggregate breakage characteristics associated with high pressure shear processes are discussed. Stress path tests were conducted to observe and analyze coarse aggregate response under complex stress states. In triaxial shear tests, it was found that peak deviator stresses increase along with confining pressures, whereas the peak principal stress ratios decrease as confining pressures increase. With increasing confining pressures, the dilation decreases and the contraction eventually prevails. Initial strength parameters (Poisson’s ratio and tangent modulus) show a nonlinear relationship with confining pressures when the pressures are relatively low. Shear strength parameters decrease with increasing confining pressures. The failure envelope lines are convex curves, with clear curvature under low confining pressures. Under moderate confining pressures, dilation is offset by particle breakage. Under high confining pressures, dilation disappears.